Impact of Electron Beam on PBAT/PLA (Ecovio) Bags by Raman spectroscopy and Thermogravimetry (Brazilian Journal of Radiation Sciences (BJRS), 2025)
Biodegradable polymers are compounds derived from renewable sources, such as biomass and organic components. They emerge as a promising alternative to reduce the environmental impact of traditional petroleum-derived polymers. These polymers have physico-chemical characteristics that allow faster degradation compared to conventional polymers, significantly reducing the time of residence in the soil and its negative impacts on the environment. Ecovio®, a sustainable and advantageous alternative, is composed of an aliphatic-aromatic copolymer Ecoflex® and polylactic acid (PLA), both biodegradable. Its formulation includes non-stick and slip agents to facilitate the processing of extrusion films. Romapack produces biodegradable bags with 55% PBAT (poly (butylenoadipate co-terephthalate)) and 45% PLA (polylactic acid) (Ecovio). In partnership with IPEN, these bags were irradiated with ionizing radiation of electron beams at absorbed doses of 25, 50 and 100 kGy to investigate possible improvements in their structure and time of degradation. Raman and thermogravimetric spectroscopy analyses were performed to observe possible changes in the polymeric chains of Ecovio bags at different doses. Thermogravimetry showed the variation of mass loss in relation to temperature and/or time, revealing improvements in relation to thermal stability. The results indicate that PLA(polylactic acid) is more susceptible to degradation compared with PBAT(poly(butylene adipate co-terephthalate)). Ionizing radiation has modified the properties of Ecovio® and expanded its range of applications, this contributes to the creation of more environmentally friendly products, as degradation contributes to their biodegradability.